A study of melt-compounded nanocomposites of polycarbonate and carbon nanotubes in the melt and solid states - Choong, Gabriel Y. H. (2014)
Polycarbonate-carbon nanotube nanocomposites are promising materials for electrostatic shielding and conductive packaging applications. The nanotubes impart electrical conductivity and increases thermal conductivity and stiffness of the matrix. However, the nanofiller also affects the rheology, and hence the evolution of a filler network during processing. This thesis examines the effects of matrix molar mass and of compounding temperature on the thermal, rheological, electrical and mechanical properties of these materials.